THE INFLUENCE OF BRAND IMAGE AND SERVICE QUALITY ON CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION IN. BOSOWA BERLIAN MOTORS IN THE CITY OF MAKASSAR - Andi Nur Ichsan Alqadri; Abdul Rahman Kadir; Nuraeni Kadir (Hasanuddin Journal of Applied Business and Entrepreneurship, 2020)
Today the competition in the business world is getting tighter, this is indicated by the number of competing companies that have sprung up that are engaged in the same type of business in capturing the market so that consumers buy the products offered and try to keep their customers so as not to turn to the same product from different companies. This study aims to analyze the effect of Brand Image and service quality on customer satisfaction, Brand Image and service quality on customer loyalty, the effect of customer satisfaction on customer loyalty, the influence of brand image and service quality on customer loyalty through customer satisfaction at PT. Bosowa Berlian Motor in Makassar city. To implement these objectives, data collection techniques are used through observation, questionnaires and documentation, using the Partial Least Square (PLS) analysis method. The results of the study found that brand image and service quality had a positive and significant effect on customer satisfaction. Brand image and service quality have a positive and significant effect on customer loyalty. Customer satisfaction has a positive and significant effect on customer loyalty. Customer satisfaction can partially mediate between brand image and service quality on customer loyalty. It can be indicated that the better the quality of service, the more satisfied the customer will be, thus impacting customer loyalty.